Zenobia: shooting star of Palmyra - Andrade, Nathanael J. (Women in antiquity, 2018)
Hailing from the Syrian city of Palmyra, a woman named Zenobia (also Bathzabbai) governed territory in the eastern Roman empire from 268 to 272. She thus became the most famous Palmyrene who ever lived. This book situates Zenobia in the social, economic, cultural, and material context of her Palmyra